Agency in Institutional Reform: Creating the Ethiopia Commodities Exchange. (8th December 2015) - Brinkerhoff, Jennifer M.
Summary: The role of agents and agency in institutional reform literature has largely been underplayed and decontextualized, even being described as a "black box." Despite calls for linking individual agency with organizational and societal analysis, the specific contours of agency remain under‐theorized. This paper presents and illustrates a framework for institutional entrepreneurism, outlining the essential role and specific actions institutional entrepreneurs can contribute to introducing, promoting, and crystallizing institutional reforms. The framework identifies how institutional entrepreneurial actions shift in their targets and responses as the resource needs change in different stages of the reform process. Using the example of establishing the Ethiopia Commodities Exchange (ECX), I illustrate each stage of institutional entrepreneurial action. The ECX experience illustrates institutional entrepreneurs as networked, political actors, who announce institutional reforms through cultural efforts that make it as easy as possible for stakeholders to comply with proposed reforms. The who and the how of agency may shift through the stages of institutional reform. The ECX experience confirms that institutional reform is political and requires engaging with both macro‐level and micro‐level politics and power. The paper closes with implications for policy and practice. Copyright © 2015 John Wiley & Sons, Ltd.